2015
DOI: 10.1002/2015ja021816
|View full text |Cite
|
Sign up to set email alerts
|

Polar cap precursor of nightside auroral oval intensifications using polar cap arcs

Abstract: Recent radar and optical observations suggested that localized fast flows in the polar cap precede disturbances within the nightside auroral oval. However, how commonly this connection occurs has been difficult to examine due to limited coverage of radar flow measurements and diffuse and dim nature of airglow patches. Polar cap arcs are also associated with fast flows in the polar cap and appear much brighter than patches, allowing evaluation of the interaction between polar cap structures and nightside aurora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 65 publications
2
14
0
Order By: Relevance
“…They found that as polar cap arcs (a) and (d) show absolute intensity and retain the faint and continuous emission from the nightside auroral oval, and the poleward boundary of the oval is identified and marked as the dashed light blue curve. Radar measurements (0-20 range gates) from SuperDARN at RKN station are also shown (Zou et al 2015) extend equatorward from high latitude, their contact with the nightside auroral poleward boundary is associated with new and substantial intensifications within the oval for 85% of the time. These intensifications statistically occur within 10 min and ±1 h MLT from the contact.…”
Section: Connection With Substorm Triggeringmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that as polar cap arcs (a) and (d) show absolute intensity and retain the faint and continuous emission from the nightside auroral oval, and the poleward boundary of the oval is identified and marked as the dashed light blue curve. Radar measurements (0-20 range gates) from SuperDARN at RKN station are also shown (Zou et al 2015) extend equatorward from high latitude, their contact with the nightside auroral poleward boundary is associated with new and substantial intensifications within the oval for 85% of the time. These intensifications statistically occur within 10 min and ±1 h MLT from the contact.…”
Section: Connection With Substorm Triggeringmentioning
confidence: 99%
“…Recently, Nishimura et al (2013) and Zou et al (2015) studied the polar cap arc-substorm relation from a different perspective, where they examined the timing when polar cap arcs contact the nightside auroral oval and the onset of substorm-like intensifications (see Fig. 23).…”
Section: Connection With Substorm Triggeringmentioning
confidence: 99%
“…Convection has been observed to be antisunward in the nightside portion of the arc and either sunward [Eriksson et al, 2006] or mixed [Liou et al, 2005] in the dayside portion of the arc. In the vicinity of polar cap arcs, convection is structured, with multiple reversals, flow shears, and flow channels [e.g., Carlson and Cowley, 2005;Eriksson et al, 2006;Zou et al, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies [ Lyons et al , ; Nishimura et al , ; Lyons et al , ; Zou et al , , ] demonstrate with complex data sets how flow channels enter, transit, and exit the polar cap. Adding to these studies, we employ DMSP passes aligned with their respective magnetic meridians.…”
Section: Discussionmentioning
confidence: 99%